Nilai Toleransi Beragama Dalam Tradisi Genduren Masyarakat Jawa Transmigran - Wahyudi Wahyudi (LP2M IAIN Palangka Raya, 2019)
This article discusses the value of tolerance in the genduren tradition, which is done by transmigrant Javanese society. The underlying problem of this study is that there are still many conflicts and acts of violence, because of differences in religious identity. The destruction of religious places of worship is a concrete evidence. This study uses a qualitative research method with a phenomenological approach as the analysis tool. The findings indicate that the behavior of genduren involved other religious people carried out by the Javanese transmigrants based on several factors. First, it is encouraged by the philosophy of Java teposeliro, one of the philosophies of Javanese society that teaches good relations with the environment, nature and fellow human beings. Second, religious models that tend to be secretive. Third, the environment developed by the predecessors is more inclusive so it opens harmonious relations with the predecessors.